Turkish Media Wildfire Coverage during the 2021 summe - BAYKAL FİDE, ECE (My University, 2021)
During the summer of 2021, wildfires emerged in several countries across the world.Although there have been obvious similarities in causes of fires, such as droughts due toclimate change, media outlets constructed narratives within their own national contexts andtheir relationships to global power structure. This framing, defined as the geopolitics ofdisaster coverage by scholars (Pantti, & Wahl-Jorgensen & Cottle 2012), promotes the use ofbanal nationalism in the language of journalism and a figure of citizen that reinforces nationstate as a locus of action rather than underlining the impact of climate change.This study claims that journalists who stuck in the national context and who didn’t refer towildfires in other countries became disconnected from the global context and thus from thegovernance of a globalized risk (Volkmer & Sharif 2018) intensified by the climate change.The sample of the study is constructed by scanning the word \"fire\" in three Turkishnewspapers: one pro-incumbent party (AKP), one pro-main opposition (CHP), and a very firstdigital journalism platform in Turkey, an independent news website, respectively Sabah, Sözcü, Bianet. It consists of 75 news picked up almost evenly from each newspaperbetween 28 July-September 1 st that covers the era starting with the first fire of the summerin Manavgat, Antalya and ending with the extinction of the fire in Dersim. This period coversalso the firefighting process in other countries such as Italy, Russia, Greece, etc. Therefore,the study aims to identify prominent framings (De Vreese, 2016) of these newspapers byanalysing how they qualify the causes of the fires: \"sabotage\", \"unintentionally caused byhumans\" \"pure impact of drought\" and \"caused by humans and intensified by the impact ofclimate change\" and as such. It seeks to question whether journalists refer to the causes ofother fires in the world. The study also analyses the debate on the preventive measures:what kind of solutions are proposed -if there are any- by journalists? Are the fires aretreated like local disasters that need local solutions or something that is also part of a globalthreat, such as climate change, and thus need both global and local adaptation andresilience policies?The study aims to underline that journalists have to overcome the national political contextas well as the use of banal nationalism in order to accomplish the requirements of a globalrisk journalism. It intends also to emphasize the significance of the journalistic interest onthe governance of the disasters intensified by the climate change.
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC)